2016
DOI: 10.1186/s12883-016-0768-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of repair of peripheral nerve transection in predegenerated muscle with and without a vein graft

Abstract: BackgroundDespite substantial research into the topic and valiant surgical efforts, reconstruction of peripheral nerve injury remains a challenging surgery. This study was conducted to evaluate the effectiveness of axonal regeneration of a transected sciatic nerve through a vein conduit containing degenerated skeletal muscle compared with axonal regeneration in a transected sciatic nerve through degenerated skeletal muscle alone.MethodsIn two of the three experimental rat groups, 10 mm of the left sciatic nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…scarring and neuroma formation, permanent loss of function), size mismatch between the donor nerve and the injured one, poor functional recovery rates and increase in surgery and anesthesia time, have prompted the interest towards the identification of surgical alternatives to this technique 5 7 . Currently, the primary option is the use of hollow nerve guide conduits that will create an adequate microenvironment for nutritional support, axon regeneration and acting as a barrier against the surrounding tissue infiltration 8 , 9 . Autologous non-nerve tissues (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…scarring and neuroma formation, permanent loss of function), size mismatch between the donor nerve and the injured one, poor functional recovery rates and increase in surgery and anesthesia time, have prompted the interest towards the identification of surgical alternatives to this technique 5 7 . Currently, the primary option is the use of hollow nerve guide conduits that will create an adequate microenvironment for nutritional support, axon regeneration and acting as a barrier against the surrounding tissue infiltration 8 , 9 . Autologous non-nerve tissues (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral nerve injury is a major problem that annually affects millions of people in the world, and most cases require surgical nerve repair (Perretta & Green, 2017). A grafting procedure is necessary to improve the functional recovery when a long segment of the nerve is lost (Mohammadi, Delaviz, Mohammadi, Delaviz, & Rad, 2016). When there is a large gap between the nerve endings, a suitable anatomical conduit is necessary so that the axons in the proximal segment can be guided into the endoneurial tubes of the distal segment and restore the function of the target organ (Iijima, Ajiki, Murayama, & Takeshita, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of published papers determined that for nerve gaps up to 4 cm in length, vein conduits did not induce any significant improvement in sensory recovery outcome compared to conduits of other materials [170]. However, the axon regeneration-promoting efficacy of vein conduits is enhanced when they are filled with PRP [171][172][173], muscle [174], pre-degenerated muscle [175,176], muscle seeded with neural-transdifferentiated human mesenchymal stem cells [177], and minced peripheral nerves [178]. One study in sheep showed that using the median epineural sheath as a conduit can restore median nerve function across 6-cm-long nerve gaps [179].…”
Section: Conduit Compositionmentioning
confidence: 99%